2015
DOI: 10.1103/physreva.91.032119
|View full text |Cite|
|
Sign up to set email alerts
|

Analytic results for the Casimir free energy between ferromagnetic metals

Abstract: We derive perturbation analytic expressions for the Casimir free energy and entropy between two dissimilar ferromagnetic plates which are applicable at arbitrarily low temperature. The dielectric properties of metals are described using either the nondissipative plasma model or the Drude model taking into account the dissipation of free charge carriers. Both cases of constant and frequency-dependent magnetic permeability are considered. It is shown that for ferromagnetic metals described by the plasma model th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…(1) tot ′ (a, T 1 , T 2 ) given by Eq. (20). For this purpose we consider the differential pressure gradient…”
Section: B Computational Results In the Experimental Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) tot ′ (a, T 1 , T 2 ) given by Eq. (20). For this purpose we consider the differential pressure gradient…”
Section: B Computational Results In the Experimental Configurationmentioning
confidence: 99%
“…As a practical matter, this means that the low-frequency response of a metal to the fluctuating electromagnetic field should be described by the lossless dielectric permittivity of the plasma model rather than by the permittivity of the lossy Drude model, which correctly describes the reaction of metals to conventional (real) fields. Moreover, for metallic plates with perfect crystal lattices the Lifshitz theory was found to be in agreement with thermodynamics only when using the plasma model, and to violate the third law of the thermodynamics (the Nernst heat theorem) when the Drude model is used [4,13,[19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…On the theoretical side, it was shown that the Lifshitz theory comes into conflict with the Nernst heat theorem when the response of metals with perfect crystal lattices to low-frequency electromagnetic fluctuations is described by the Drude model. This was proven in different geometries for the Casimir interaction between nonmagnetic [44][45][46][47][48] and magnetic [49] metals and, very recently, for the Casimir-Polder interaction of both polarizable and magnetizable atoms interacting with metallic plate [50].…”
Section: Introductionmentioning
confidence: 88%
“…This means that the dissipationless plasma model, which is in fact applicable only at high frequencies in the region of infrared optics, works well for some reasons even at low frequencies characteristic of the normal skin effect. The problem is aggravated by the fact that for metals with perfect crystal lattices the Casimir entropy calculated within the Lifshitz theory using the Drude model violates the Nernst heat theorem although the same satisfies it if the plasma model is used [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%